Implementation of Occupational Safety and Health to Facility Team Employees at Conrad Bali Hotel - Jaya, Komang Antara; wulan, Anak Agung Istri Ratna Sari (Program Studi Manajemen Divisi Kamar, 2025)
This study explores the implementation of occupational safety and health practices for facility team employees at Conrad Bali Hotel. Using a qualitative descriptive method, data were collected through in-depth interviews with the Executive Housekeeper, Facility Supervisor, and facility team members, as well as document analysis. The analysis was guided by five ISO 45001:2018 indicators: policy and commitment, risk identification and assessment, training, risk control and use of personal protective equipment (PPE), and monitoring and evaluation. The findings indicate that occupational safety and health has been effectively implemented in terms of policy and commitment, risk identification and assessment, and training. However, risk control, PPE compliance, and monitoring and evaluation remain suboptimal, with inconsistencies in employee adherence and insufficient supervision. The study recommends the establishment of clearer written guidelines, stricter enforcement, and continuous evaluation to strengthen the overall occupational safety and health system. Improving these aspects will enhance employee safety, minimize occupational risks, and contribute to sustainable hotel operations.